TAUHID DAN REVOLUSI MENTAL - Nur Sidik (UIN Raden Mas Said Surakarta, 2015)
Islam can be called as a teacher of civilation which is taughtabout tauhid. Tauhid brought the intention of our foundingfathers/mothers to proclaime the Indonesia‟s indepence. The foundingfathers/mothers have seriously aware about the importance of puttingtauhid as spirit of Pancasila. Hereby, the duty of the next generation isto refresh the tauhid‟s understanding and experiences as spirit of state‟sidentity. By utilizing the spirit of tauhid as life and thinking paradigmis expected would be able to make Indonesia be better off from seriousthreat caused by imperalism, otoritarian rejim, materialism andhedonism life style which is contractied to the western culture.